The effect of task difficulty on decision-making: Differences between obsessive–compulsive disorder and non-affective psychosis. Issue 3 (1st August 2018) - Serrano-Guerrero, Estrella; Rodríguez-Testal, Juan Francisco; Martín-Rodríguez, Agustín; Ruiz-Veguilla, Miguel
The aim was to determine whether there are differences between groups in jumping to conclusions and the number of beads required to make a decision based on task difficulty. An assessment was made of 19 patients with non-affective psychosis, 19 with obsessive–compulsive disorder (OCD), and 19 healthy controls. The Beads Task scale was used in its two versions. Patients with non-affective psychosis jumped to conclusions. There was significant interaction between group and task difficulty. Increased difficulty of the task did not affect the number of beads patients with non-affective psychosis or OCD needed to make their decision. However, healthy controls needed to see more beads before they could make a decision in the hard test than in the easy one. Patients with non-affective psychosis jump to conclusions, but neither this group nor the OCD patients benefit from the changes in task difficulty when making their decisions.